Measurement of the [Formula: see text] meson lifetime using [Formula: see text] decays. - Aaij, R; Adeva, B; Adinolfi, M; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Cartelle, P; Alves, A; et al. (2014)
The lifetime of the [Formula: see text] meson is measured using semileptonic decays having a [Formula: see text] meson and a muon in the final state. The data, corresponding to an integrated luminosity of [Formula: see text], are collected by the LHCb detector in [Formula: see text] collisions at a centre-of-mass energy of 8 TeV. The measured lifetime is [Formula: see text]where the first uncertainty is statistical and the second is systematic.